Hexaferrite-based permanent magnets with upper magnetic properties by cold sintering process via a non-aqueous solvent. (15th October 2021) - Serrano, Aida; García-Martín, Eduardo; Granados-Miralles, Cecilia; Gorni, Giulio; López-Sánchez, Jesús; Ruiz-Gómez, Sandra; Pérez, Lucas; Quesada, Adrián; Fernández, José F.
Abstract: The incessant technological pursuit towards a more sustainable and green future depends strongly on permanent magnets. At present, their use is widespread, making it imperative to develop new processing methods that generate highly competitive magnetic properties reducing the fabrication temperatures and costs. Herein, a novel strategy for developing dense sintered magnets based on Sr-hexaferrites with upper functional characteristics is presented. An innovative cold sintering approach using glacial acetic acid as novelty, followed by a post-annealing at 1100 °C, achieves a densification of the ceramic magnets of 92% with respect to the theoretical density and allows controlling the particle growth. After the cold sintering process, a fraction of amorphous SrO is identified, in addition to a partial transformation to α-Fe2 O3 as secondary crystalline phase. 46 wt% of SrFe12 O19 remains, which is mostly recuperated after the post-thermal treatment. These findings do not significantly modify the final structure of ferrite magnets, neither at short- nor long-range order. The innovative process has a positive impact on the magnetic properties, yielding competitive ferrite magnets at lower sintering temperatures with an energy efficiency of at least 25%, which opens up a new horizon in the field of rare-earth free permanent magnets and new possibilities in other applications. Graphical abstract: Image, graphical abstract